Subtitle Translation from a Multimodal Perspective: Text and Visual Integration in Animated Film - Ali, Sri Widyarti (Universitas Nurul Jadid, 2024)
The global appeal of animated films has increased significantly, leading to an urgent demand for high-quality and easily comprehensible subtitle translations. This research investigates the complexities of subtitle translation in the animated film Frozen (2013) by exploring the interaction between visual elements and dialogue. Employing multimodal discourse analysis, the study evaluates how subtitles can enhance or diminish the narrative experience by aligning with or diverging from the film’s visual context. The findings indicate that while translations generally capture the intended meaning and tone, there are critical moments—especially in humorous scenes—where subtitles fail to fully resonate with the accompanying visuals. This misalignment underscores the importance of a refined approach to translation that considers the interplay of various expressive modes. The research ultimately aims to contribute to best practices in audiovisual translation, emphasizing the need for coherence between subtitles and visual storytelling to enrich audience engagement.